Sistemática de “Trichopsychodina” Ježek, 1985 (Diptera, Psychodidae, Psychodinae) - Vieira, Cínthia Barrêto Chagas (Instituto Nacional de Pesquisas da Amazônia - INPA, 2020)
Psychodidae consists of 130 genera and approximately 3000 species, distributed in all continents except Antarctica. Psychodidae is divided into six subfamilies: Bruchomyiinae, Horaiellinae, Phlebotominae, Psychodinae, Sycoracinae and Trichomyiinae. Psychodinae is cosmopolitan and diverse, and its suprageneric classification is controversial due to the similarity between genera. This thesis presents a phylogenetic study of "Trichopsychodina", based on 146 morphological characters of adult males of 137 species (106 species of ingroup and 31 species of outgroup). Most of the specimens studied are holotypes and/or paratypes. The parsimony analysis was done using two algorithms of the “new technology” of TNT: Tree Drifting and Ratchet. The initial search of 300 RAS + TBR resulted in 10 trees of 2048 steps in lenght. With the inclusion of 2500 interactions of Ratchet parsimony, were found 544 trees of 2044 steps and after 2500 cycles of Tree Drifting completed the number of equally parsimonious trees increased to 959. According to the results based on the strict consensus tree, Trichopsychodina is not a monophyletic group and genera that belonged to this subtribe now are allocated in Psychodini, which is supported by two autapomorphies (a row of larger alveoli at the apex of the bridge starting on the eye and the presence of a posterior arm of ascoid) and 12 homoplasies. In this proposal, Psychodini contains 13 genera, 4 of these new: Wagnermyia gen. nov. (type-species Wagnermyia calabens comb. nov.), Neartika gen. nov. (type-species Neartika jonesi comb. nov.), Neotropikos gen. nov. (type-species Neartika sextenaculus sp. nov.) e Applanatus gen. nov. (type-species Applanatus banksi comb. nov.). Although it was not possible to analyze specimens of Epacretron and Neomaruina, these genera were kept in Psychodini, because they have a series of characters that delimit the tribe. On the consensus tree, the following topology was found: (Wagnermyia (Neartika (Neotropikos ((Trichopsychoda + Threticus) (Feuerborniella (((Rhipidopsychoda + Applanatus) Psychoda s.l.) (Quatiella + Philosepedon)))))))). In this thesis, 24 new species are described and 27 species are transferred.